Perencanaan Pembangunan Pariwisata di Kabupaten Kutai Kartanegara (Studi pada Dinas Kebudayaan dan Pariwisata Kabupaten Kutai Kartanegara) - Amin, Muhammad (Jurnal Ilmiah Administrasi Publik, 2017)
This research aims to analyze the process of preparing and determining the planning of tourism development by using T-A-I-D Tracking, analizing, amaging and deciding on the planning of tourism development of Kutai Kartanegara regency. With the aim of carrying out the process of preparation and determination needs to be supported by various parties and SKPD in order to accomplish the proses of determining the development is running in integrity with attention to several factors that can affect the process of determining the development.